La industrialización y su incidencia en el crecimiento económico de América Latina: Un análisis de datos panel, periodo 1990-2020 - Guaicha Cabrera, Thalia Alexandra (2023)
The industrialization process is one of the main sectors to generate economic growth within a country, in recent years Latin America has had an economic growth of 66,487.95 billion dollars in 2010 and in 2019 its economic growth was of 87,283.6 billion dollars, however it has been particularly affected by the COVID-19 pandemic. Therefore, the objective of this research is to determine the incidence of the industry in economic growth in Latin America, during the period 1990-2020. The methodology used consists of a Generalized Least Squares (GLS) model that determines the relationship of the variables; a cointegration test to identify if there is a short- and long-term relationship and a Dumitrescu and Hurlin causality test. Resulting in a positive relationship between the variables considered, in the same way, it is evident that the industry is positively related to economic growth in the short and long term; however, it is verified that there is no bidirectional causality between the variables, that is, that economic growth does not cause industry and industry does not cause economic growth, concluding that other sectors of the economy can directly affect economic growth. Among policy implications, it is proposed to encourage and intensify the industry, thus contributing to the economic growth of Latin American countries.